ELISA detection of Apple chlorotic leafspot virus (ACLSV) and Apple mosaic virus (ApMV) in comparison to RT-PCR detection and the determination of genetic variation of these virus species in South Africa - Malan, Sophia Susanna (Stellenbosch : Stellenbosch University, 2015)
Thesis (MScAgric)--Stellenbosch University, 2014.